2023
DOI: 10.1088/1755-1315/1230/1/012122
|View full text |Cite
|
Sign up to set email alerts
|

Performance of agronomic characteristics and path analysis of the highland new plant types of rice

Y L Limbongan,
Driyunitha,
T Y Parari
et al.

Abstract: This study aims to examine the good production characteristics and path analyses as well as the character correlation of the highland F4 new plant type of lines. The research was conducted in four paddy fields, namely Bittuang, Rantebua, Sesean, and Tallunglipu sub-districts at altitudes of 650, 850, 1400 and 1600 meters above sea level in North Toraja and Tana Toraja Regencies. This research took place from June to December 2021 and was arranged in randomized block design. The genotypes tested were 30 F4 line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…In addition, Roy et al (2015) reported the positive impact of effective tiller number per plant on the final yield. Similar findings have been obtained in many studies in rice (Oladosu et al, 2018;Limbongan et al, 2023;Reddy et al, 2023).…”
Section: Traits That Similarly and Directly Affected The Grain Yield ...supporting
confidence: 91%
See 1 more Smart Citation
“…In addition, Roy et al (2015) reported the positive impact of effective tiller number per plant on the final yield. Similar findings have been obtained in many studies in rice (Oladosu et al, 2018;Limbongan et al, 2023;Reddy et al, 2023).…”
Section: Traits That Similarly and Directly Affected The Grain Yield ...supporting
confidence: 91%
“…The selection of traits for crop improvement is a complex decision-making process. The promising results of path analysis, as evidenced by previous studies on rice, emphasise its efficacy in guiding selection strategies (Shahidullah et al, 2009;Oladosu et al, 2018;Al-Musawi et al, 2019;Laxmi et al, 2023;Limbongan et al, 2023;Reddy et al, 2023). By presenting the direct and indirect effects of various traits, path analysis elucidates the hierarchical order of trait contributions, and it aids in identifying positive indicators for yield increment and potential negative yield indicators.…”
Section: March 2024mentioning
confidence: 99%